Relación entre psicólogos y estudiantes usuarios en el 2014: factor determinante en los servicios de prevención de adicciones de la Universidad de Antioquia - Isabel Cristina Orozco-Giraldo; Isabel Cristina Posada-Zapata; Eliana María Hernández-Ramírez (Universidad de Antioquia, 2018)
Objective: To describe the relationship between psychologists and student users who attended the addiction prevention program offered by Universidad de Antioquia, at the Medellin campus, in 2014, and its influence on the perception of the quality of the program. Methodology: A qualitative research was conducted using tools of the method known as Grounded Theory. The primary information sources of this study were discourses resulting from interviews with students who had accessed the program. The Collection tools were a semi-structured interview and an in-depth interview. Results: Perceived program quality is conditioned significantly by the relationship between psychologists and student users, taking into account, on the part of the latter, aspects as a positive perception of services and the fulfillment of their needs and expectations. Conclusion: Good treatment, kindness and the trust that psychologists build with student users are recognized as determining elements in continuing the process and in service quality perception.